2009
DOI: 10.1111/j.1399-3054.2009.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Aox gene structure, transcript variation and expression in plants

Abstract: Alternative oxidase (Aox) has been proposed as a functional marker for breeding stress tolerant plant varieties. This requires presence of polymorphic Aox allele sequences in plants that affect plant phenotype in a recognizable way. In this review, we examine the hypothesis that organization of genomic Aox sequences and gene expression patterns are highly variable in relation to the possibility that such a variation may allow development of Aox functional markers in plants. Aox is encoded by a small multigene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 86 publications
5
75
0
Order By: Relevance
“…It is well documented that AOX1s could be induced by various biotic and abiotic stresses, whereas AOX2 is usually developmentally expressed and constitutively regulated by environmental factors (Polidoros et al, 2009). Many studies have indicated that the lack of AOX1 reduces the tolerance or growth ability under stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that AOX1s could be induced by various biotic and abiotic stresses, whereas AOX2 is usually developmentally expressed and constitutively regulated by environmental factors (Polidoros et al, 2009). Many studies have indicated that the lack of AOX1 reduces the tolerance or growth ability under stress.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on various transgenic plants indicate that these isoforms are not redundant and cannot compensate for each other under stress or adverse growth conditions (Table I). These include studies on Arabidopsis (Arabidopsis thaliana), which has five nuclear AOX genes: four AOX1 type (A-D) and one AOX2 type (Polidoros et al, 2009). In Arabidopsis, an aox1a knockout cannot be compensated by the expression of other isogenes (Table I; Strodtkötter et al, 2009;Kühn et al, 2015).…”
mentioning
confidence: 99%
“…In plants, it is possible for electron transport to O 2 to occur in the presence of light through thylakoidal membranes of chloroplasts, via chlororespiration (Figure 3) (Polidoros et al, 2009), distinct from photorespiration (Bennoun, 1982;Peltier and Cournac, 2002) and the Mehler reaction. The function of this process is to ensure supplies of ATP and NAD(P)H generated by glycolysis for converting starch into triose phosphate (D-glyceraldehyde phosphate or dihydroxyacetone phosphate) (Bauwe et al, 2010;Maurino and Peterhansel, 2010).…”
Section: Chlororespirationmentioning
confidence: 99%
“…Studies have elucidated a crucial role of AOX in protecting against ROS produced during oxidative stress (van Dongen et al, 2011), and it can also influence mitochondrial adaptability to different kinds of stress (Moller, 2001;Rasmusson et al, 2009), even expressing mitochondrial genes in a wide variety of environments. AOX acts against ROS as follows: AOX allows electron transfer from ubiquinone (UQ) to O 2 , which high levels of reducing agents in the UQ pool can be dissipated through AOX, thus avoiding the formation of ROS (Polidoros et al, 2009). …”
Section: Oxidative Phosphorylation In Plantsmentioning
confidence: 99%